Emotional Stability and Self-Control: A Case Study of University Taekwondo Athletes - Ramadhani, Raisya Nurkhalida; Komarudin , Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
In taekwondo matches, some taekwondo athletes have difficulty managing their emotions and self-control when experiencing unexpected things in the middle of the game, this makes athletes lose focus on their match so athletes have a lack of confidence and damage the match pattern that has been planned before the game starts, such as kicking that does not hit the point repeatedly, and not protecting the body protector properly. This results in athletes experiencing defeat in the match which adds to the emotions of athletes becoming increasingly mixed up and unable to control themselves. Existing studies are still limited in examining the relationship between emotional stability and self-control in university taekwondo athletes. Therefore, this study aims to fill this gap by examining the relationship between the two variables in university taekwondo athletes, The researcher also aims to test the relationship between emotional stability and self-control in university taekwondo athletes. This study uses a descriptive method with a quantitative approach involving 30 taekwondo athletes from the Indonesian Education University. The instruments used in this study are cross-sectional taken from the UWIST Mood Adjective Checklist (UMAC) and Brief Self-Control Scale. After the data has been obtained, data analysis is carried out by correlation testing using SPSS 25. The results of the study showed that there was a significant relationship between the emotional stability and self-control of university taekwondo athletes. This study concludes that emotional stability and self-control play an important role in the self-control of university taekwondo athletes.